2002
DOI: 10.1289/ehp.02110655
|View full text |Cite
|
Sign up to set email alerts
|

Apartment residents' and day care workers' exposures to tetrachloroethylene and deficits in visual contrast sensitivity.

Abstract: Tetrachloroethylene (also called perchloroethylene, or perc), a volatile organic compound, has been the predominant solvent used by the dry-cleaning industry for many years. The U.S. Environmental Protection Agency (EPA) classified perc as a hazardous air pollutant because of its potential adverse impact on human health. Several occupational studies have indicated that chronic, airborne perc exposure adversely affects neurobehavioral functions in workers, particularly visual color discrimination and tasks depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 80 publications
5
99
1
1
Order By: Relevance
“…We found and report no consistent effect of residential perc exposure on adult VCS at the highest levels of indoor air perc found (up to about 700 µg/m 3 (NYS DOH, 2010). This is not inconsistent with other residential studies of adults that found either no neurobehavioral effects or effects only at higher levels of exposure than found in our study (Altmann et al, 1995;Schreiber et al, 2002;Storm & Mazor, 2004).…”
Section: Letter To the Editorcontrasting
confidence: 58%
See 1 more Smart Citation
“…We found and report no consistent effect of residential perc exposure on adult VCS at the highest levels of indoor air perc found (up to about 700 µg/m 3 (NYS DOH, 2010). This is not inconsistent with other residential studies of adults that found either no neurobehavioral effects or effects only at higher levels of exposure than found in our study (Altmann et al, 1995;Schreiber et al, 2002;Storm & Mazor, 2004).…”
Section: Letter To the Editorcontrasting
confidence: 58%
“…However, selection bias was minimized by our recruitment methods. Earlier research had shown that perc exposures might be elevated in some, but not all, residential buildings where a dry cleaner using perc was colocated, and that vision in adults might be harmed by such exposures (Altmann et al, 1995;Schreiber et al, 2002). Other research suggests that children might be more affected by exposure to environmental contaminants, including perc, than adults (Needham & Sexton, 2000;Stein et al, 2002;Schwenk et al, 2003).…”
Section: Dear Sirmentioning
confidence: 99%
“…For PCE, neurotoxicity is the most sensitive outcome of exposure in humans, where toxicity is observed even at low-exposure concentrations. For instance, perturbations in visual contrast sensitivity have been observed with chronic exposure to as little as 0.3 ppm PCE (Schreiber et al, 2002;New York State Department of Health, 2010), whereas effects in other organs (e.g., liver or kidney) are not observed until airborne concentrations of PCE are at least two to three orders-of-magnitude higher (US EPA, 2011a). A very recent study reported an increased risk of epilepsy in humans exposed to PCE through contaminated public water supplies during gestation or early childhood (Aschengrau et al, 2015).…”
Section: Noncancer Toxicitymentioning
confidence: 99%
“…Aufgrund der Lipophilie wurde der höchste Gewebe-Blut-Verteilungskoeffizient in vitro erwartungsgemäß für Fettgewebe (125) ermittelt im Vergleich zu Niere, Leber, Muskel (5-6) [17]. Tetrachlorethen konnte in humaner Muttermilch nachgewiesen werden [17][18][19].…”
Section: Aufnahme Verteilungunclassified